The Relationship Between E-Cigarette Use and Propylene Glycol Content in Women Aged 17–25 Years with the FEV1 and FVC Ratios in Relation to Copd in South Jakarta and its Analysis from an Islamic Perspective - Damarasri, Indira; Yuliadi, Teguh; Fitri, Fitri; Zen, Irwandi M. (Jurnal Indonesia Sosial Sains, 2026)
This research aims to investigate the relationship between e-cigarette use, propylene glycol content, and the FEV1/FVC ratio in women aged 17–25 years in South Jakarta, as well as to analyze the findings from an Islamic health ethics perspective. A cross-sectional analytical study was conducted involving 40 female e-cigarette users aged 17–25 years in South Jakarta. Data were collected using spirometry to measure FEV1 and FVC, and a structured questionnaire to assess e-cigarette usage patterns and PG exposure. Purposive sampling was applied, and data were analyzed using descriptive and correlational statistics. All respondents showed FEV1/FVC ratios within normal limits (>75%), with no significant correlation found between the duration or intensity of e-cigarette use and lung function decline. Variations in usage patterns (puffs per day, liquid consumption) did not demonstrate a clear association with FEV1/FVC outcomes. Additionally, no meaningful relationship was observed between e-cigarette use and menstrual pain history. Although e-cigarette use among young women in this sample did not show immediate adverse effects on lung function as measured by FEV1/FVC, potential long-term risks remain a concern. From an Islamic perspective, e-cigarette use may be considered makruh or even haram if proven harmful to health, aligning with the principle of preserving well-being (hifz al-nafs) and avoiding harm (darar). These findings highlight the need for continuous health monitoring and religiously informed public health messaging regarding e-cigarette use.